RETROSPECTIVE ET ANALYSE DEMOGRAPHIQUE DE LA DYNAMIQUE URBAINE DU SYSTEME WILAYAL TEBESSI (1966–2008) - MEDARAG NAROU BOUBIR HANA; FARHI ABDELLAH (Revue Roumaine de Géographie)
Empirical studies have shown regularities in the medium and long-term evolution of urban populations. Local fluctuations of the population of each city are opposed by the high stability of the hierarchical organization of these cities, in terms of statistical distribution by city size. Our goal is to describe and understand the evolutionary behaviour of the system at Tebessa over short and long-term periods using the rank-size distribution of its elements. And also to verify the permanence of secondary Zipf’s law in the case of the wilayaof Tebessa. The observation of the manifestations of the dynamics of Tebessa from 1966 to 2008 reveals it to be macrocephalous and unbalanced, but the size distribution of its elements remains relatively stable over time. The Tebessa strongly hierarchical system does not conform to Zipf’s law.